A Case Study On Genting Berhad - N., Raja Segaran (2006)
This study is focused on genting Berhad, a conglomerate listed in the Main Board of Bursa Malaysia. Analysis is based on environmental scanning of Genting Berhad and followed by strategy formulation, strategy implementation and its evaluation and control.